Adsorventes compostos de ferro, alumínio e lantânio: síntese, caracterização e aplicação na remoção de fluoretos - Gasparotto, Juliana Machado (2022)
The use of groundwater to obtain water for human consumption is an alternative for places where there is no nearby surface spring available, or where there is no water treated by concessionaires being distributed to population. Fluoride is an ion commonly found in underground sources, which when consumed in concentrations that exceed the limits established by the WHO and Brazilian legislation on water potability (1.5 mg. L-¹), for prolonged periods, can cause damage to health. Among the methodologies for fluoride removal, adsorption is a technique that stands out for being one of the most efficient in terms of cost, design, and operation. Although adsorbents with consolidated commercial use already exist, such as alumina, the development of new materials for specific application in groundwater has become a challenge. In this work, Fe-Al-La trioxide hydrated adsorbents, pure and supported on granular alumina were synthesized, characterized, and tested for fluoride removal from water. A Rotational Central Composite Design was performed for two factors (pH and adsorbent dosage), with response surface methodology, and the results for the pure adsorbent showed that the material presents fluoride adsorption property in the pH range from 4 to 10, with ideal pH at 8.25, and the adsorbent dosage defined as ideal for the following experiments was 1.5 g L−¹. The obtained results for the percentage removal for Fe-Al-La supported-on alumina made it possible to find the ideal conditions for the kinetic and equilibrium tests: 3.0 g L-¹ of adsorbent dosage and pH of 6.5. Subsequently, assays of fluoride adsorption kinetics and isotherms were carried out. The kinetics of adsorption tests showed that the kinetic model of linear driving force was the one that most adequately described the kinetics of fluoride adsorption for the pure adsorbent, while it was Avrami for the adsorbent supported on alumina, presenting R2 values ≥ 0.99 in both cases. The results of the fluoride adsorption isotherm tests indicated that the Langmuir isotherm model fitted better to the experimental data for the two adsorbents, reaching qmax of 28.06 mg g-¹ and 8.170 mg g-¹ for pure and supported adsorbent, respectively. A study was carried out with groundwater obtained from a well in Faxinal do Soturno/RS, using the pure adsorbent and under experimental conditions of room temperature, natural pH of the water, and adsorbent dosage of 1.5 mg L-¹, and as a result an average removal of 52% was reached in one hour of adsorption. Also, the effect of interfering ions was evaluated for the alumina-supported adsorbent, and the following order of ionic affinity of the adsorbent was found F- > SO4 ²- > Cl- > NO3-. It is concluded that the Fe-Al-La adsorbent, when pure, has a much greater adsorption capacity than when supported on alumina, demonstrating a high potential to be used in the removal of fluorides from groundwater.